2012
DOI: 10.1017/s0008423911000953
|View full text |Cite
|
Sign up to set email alerts
|

To Prosecute or Not to Prosecute, That is the Question: Agency Litigation under the Influence of Appellate Courts

Abstract: Abstract. This article examines how institutional uncertainty within the US federal circuit courts influences regulatory agencies' enforcement choices of prosecution or non-prosecution. I argue that the circuits' random assignment of judges and cases creates institutional uncertainty in terms of variation in each circuit's possible rulings with respect to the bureaucracy's policy position. This, in turn, affects agencies' probability of prosecution because the high degree of uncertainty will discourage prosecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Another study indicated that regulatory agencies can avoid exposing themselves to judicial review by not bringing to justice cases with little chance of success due to contrary (LI, 2012). Much of the literature focuses on the outcome of administrative proceedings examined by courts, but in this case the author analyzed procedures and investigations (carried out by an antitrust agency) that were closed at the administrative level.…”
Section: Calculated Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that regulatory agencies can avoid exposing themselves to judicial review by not bringing to justice cases with little chance of success due to contrary (LI, 2012). Much of the literature focuses on the outcome of administrative proceedings examined by courts, but in this case the author analyzed procedures and investigations (carried out by an antitrust agency) that were closed at the administrative level.…”
Section: Calculated Behaviorsmentioning
confidence: 99%
“…This discussion goes beyond the debate on the judicialization of public policies, which focuses on the institutional role of judges and courts from the moment they are provoked to deliberate on such policies (COUTINHO, 2013). According to some studies, the possibility of judicial review has major effects on administrative decisions and can trigger defensive behavior on the part of regulatory agencies (LI, 2012;DRAGU and BOARD, 2015). In addition, the judicialization of public policies still focuses on social and constitutional issues, while regulatory matters raise tensions that are yet to be studied (GINSBURG, 2009).…”
Section: Introductionmentioning
confidence: 99%